Patient Safety Culture And Its Impact On Nursing Practice In Saudi Healthcare Settings (The Review of Diabetic Studies, 2024)
Introduction:  Patient Safety Culture (PSC) is a set of values, attitudes, and behavioural patterns of healthcare workers with regards to avoiding the medical harm. In the Kingdom of Saudi Arabia (KSA), the development of a strong PSC is a strategic plan of the Saudi Vision 2030 program of Healthcare Sector Transformation, which will help to convert national facilities into high-reliability organizations. The clinical environment is now becoming a challenge to the nursing, where clinical risks are the modulating factor on the outcomes and in this case, a five-year record of medical error claims has increased by 37 percent.Study Objective: The primary objective of this systematic review is to systematically review and synthesize existing findings regarding Patient Safety Culture (PSC) in the Saudi Arabian healthcare context, specifically looking at how PSC influences Nursing Practice.Methodology: A systematic search information in PubMed, Scopus, CINAHL, and the Saudi Digital Library was performed on peer-reviewed articles published in the past 5 years (between 2000 and 2025). The Joanna Briggs Institute (JBI) and AXIS critical appraisal tools had been used to evaluate methodological quality. Thematically based narrative synthesis was used to analyze data of 17-21 eligible studies including the latest national HSPSC cycles.Conclusion: The results show that the Saudi hospitals have a moderate degree of patient safety culture. In Teamwork in Units (82.95%-88%), and Organizational Learning (81.88%-89%) one always finds national strengths, good communication climate scores are the main predictor of patient satisfaction. On the contrary, there are still critical systemic weaknesses with Non-punitive Response to Error (12%-43.89%) and Staffing (20.9%-40.1%). The quantitative evidence shows that teamwork and communication can explain 48 percent of the variation in the incident reporting rates, and high perceptions of PSC are correlated with a more significant decrease in the rate of pressure ulcer incidence (OR 0.86) and adverse drug events (OR 0.83).